Preparation method and application of high-dispersion lithium-rich manganese-based positive electrode material
The lithium-rich manganese-based positive electrode material was prepared by co-precipitation reaction and spray drying, which solved the problems of high energy consumption and insufficient electrochemical performance caused by high temperature hydrothermal reaction in the existing methods, and achieved the preparation of materials with high dispersion and excellent electrochemical performance.
Patent Information
- Application Number
- CN202411852355.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-16
AI Technical Summary
The existing preparation methods for lithium-rich manganese-based positive electrode materials require high temperature hydrothermal reactions, high energy consumption and element doping, resulting in insufficient electrochemical performance and cycle stability.
The precursor of lithium-rich manganese-based positive electrode material was prepared by co-precipitation reaction, and the solvent was removed by spray drying, followed by mixing with the flux and sintering in an air atmosphere, optimizing the preparation conditions to improve dispersion and electrochemical properties.
The preparation of highly dispersible lithium-rich manganese-based cathode material at lower temperatures is achieved, which improves its electrochemical performance and cycle stability, reduces energy consumption, and simplifies the process flow.
Smart Images

Figure CN119660826A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electrochemical materials, and in particular relates to a preparation method of a highly dispersed lithium-rich manganese-based positive electrode material and an application thereof. Background Art
[0002] Lithium-ion batteries have become the most widely used battery system in the new energy vehicle industry due to their advantages of high specific capacity, high operating voltage and long cycle life. In lithium-ion batteries, the positive electrode material not only accounts for the majority of the total cost of the battery pack, but the capacity and life of the positive electrode material are also important parameters that restrict the performance of lithium-ion batteries. At present, the commercialized positive electrode materials mainly include ternary (NCM, NCA) system, lithium iron phosphate (LFP) system and lithium manganese oxide system. In comparison, lithium-rich manganese-based positive electrode materials have a specific capacity of more than 300mAh / g, which can greatly improve the energy density of lithium-ion batteries. As a layered metal oxide positive electrode containing a small amount of rare and expensive metal elements such as nickel and cobalt, lithium-rich manganese-based positive electrodes have become one of the important development directions of the next generation of positive electrode materials. Molten salt technology uses liquid reaction media to achieve atomic-level mixing of reactants, allowing crystals to nucleate and grow uniformly from the flux at a relatively low temperature, thereby reducing lithium loss during the synthesis process and improving the uniformity and quality of the sample.
[0003] Patent CN116971021A discloses a method for preparing a doped single-crystal lithium-rich manganese-based positive electrode material by a hydrothermal method-molten salt-assisted method, wherein a carbonate precipitant is weighed in a molar amount of 1 to 2 times the total molar amount of manganese salt, nickel salt and cobalt salt and fully dissolved in water to obtain solution B; solution B is poured into solution A and fully stirred to obtain a suspension containing a precipitate; the suspension is transferred to a hydrothermal kettle, and hydrothermal treatment is performed at a preset temperature for a predetermined time, and a precursor is obtained after a washing process; the precursor, lithium salt, flux and dopant are mixed and ground according to a preset ratio and then sintered, and the obtained sample is washed, filtered and dried to obtain a doped single-crystal lithium-rich manganese-based positive electrode material. However, this scheme requires element doping to obtain a lithium-rich manganese-based positive electrode material with good capacity and cycle performance, and it requires a high-temperature hydrothermal reaction and high energy consumption. Therefore, it is necessary to provide an improved method for preparing a lithium-rich manganese-based positive electrode material to solve the above problems. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a highly dispersed lithium-rich manganese-based positive electrode material and its application. By optimizing the preparation process, a lithium-rich manganese-based positive electrode material with good dispersion, excellent electrochemical performance and cycle stability is obtained.
[0005] To achieve the above object, the present invention provides a method for preparing a highly dispersed lithium-rich manganese-based positive electrode material, comprising the following steps:
[0006] S1, introducing a transition metal salt solution, a precipitant, and a complexing agent into a reaction container, performing a coprecipitation reaction and then performing crystallization to obtain a lithium-rich manganese-based positive electrode material precursor; the transition metal salt includes a manganese salt, a nickel salt, and a cobalt salt;
[0007] S2, mixing the precursor and the lithium source in a solvent by ball milling according to a stoichiometric ratio, and spray drying the mixed slurry to remove the solvent;
[0008] S3, mixing the mixture obtained by spray drying with a flux evenly and then sintering in an air atmosphere, washing and drying the sintered product to obtain a lithium-rich manganese-based positive electrode material.
[0009] Furthermore, the chemical formula of the lithium-rich manganese-based positive electrode material is Li 1.2 Mn x Ni y Co (0.8-x-y) O 2 , where 0.5≤x≤0.6, 0.1≤y≤0.2. Each raw material satisfies the product Li 1.2 Mn x Ni y Co (0.8-x-y) O 2 The stoichiometric ratio.
[0010] Furthermore, the pH value of the coprecipitation reaction is 7.5-8.5, and the reaction is continuously stirred at 40-60°C for 24-48 hours; in step S2, the inlet temperature of the spray drying is 135-145°C.
[0011] Further, in step S2, the lithium source is at least one of lithium carbonate, lithium hydroxide, and lithium oxide;
[0012] And / or, the solvent is at least one of water, ethanol, methanol and isopropanol, and the solid content in the solvent is 10-20wt%; the ball milling time is 5-12h, preferably 8-10h.
[0013] Further, in step S3, the sintering includes: heating to 500°C-600°C at 2-10°C / min, and keeping warm for 4-6 hours; then heating to 800°C-900°C at 2-10°C / min, and keeping warm for 10-14 hours; preferably, finally cooling to 250°C-350°C at 2-10°C / min, keeping warm for 2-4 hours, and then cooling naturally.
[0014] Furthermore, in step S1, the nickel salt is at least one of nickel sulfate and nickel acetate; the manganese salt is at least one of manganese sulfate and manganese acetate; the cobalt salt is at least one of cobalt sulfate and cobalt acetate, and the total concentration of metal ions is 1 to 3 mol / L.
[0015] Furthermore, in step S1, the precipitating agent is at least one of sodium carbonate, potassium carbonate, sodium hydroxide, and potassium hydroxide, and the concentration is 1.5 to 3 mol / L; the complexing agent is at least one of ammonium carbonate, ammonium sulfate, and ammonium bicarbonate, and the concentration is 0.5 to 2 mol / L.
[0016] Furthermore, in step S3, the flux is at least one of sodium chloride, potassium chloride, lithium chloride and lithium nitrate, and the addition ratio is 3 to 8 times the mass of the spray drying collected product.
[0017] The present invention also provides a highly dispersed lithium-rich manganese-based positive electrode material, which is prepared by any of the preparation methods described above.
[0018] The present invention also provides an application of a highly dispersed lithium-rich manganese-based positive electrode material as a positive electrode of a lithium-ion battery.
[0019] In general, the above technical solution conceived by the present invention has the following technical advantages compared with the prior art:
[0020] 1. The present invention provides a method for preparing a highly dispersed lithium-rich manganese-based positive electrode material, which uses a spray drying method to obtain a raw material mixture with ultrafine particle size and good dispersibility, so that the particle size of the final product is mainly distributed in the range of 300 to 500 nm, thereby obtaining excellent electrochemical performance.
[0021] 2. The present invention uses a suitable flux to provide a molten salt environment, the energy required for the lithium source to overcome during the calcination process is reduced, and the flux is completely removed in subsequent treatments, which will not have an adverse effect on crystallinity and electrochemical properties. The preparation uses an environmentally friendly flux for easy recycling, and at the same time has a lower sintering temperature, low cost, good economic benefits, is conducive to industrial application, and has a good application prospect in lithium-ion batteries.
[0022] 3. The present invention only needs to prepare the precursor at a relatively low temperature, the reaction conditions are mild, energy consumption is saved, and it is helpful to homogenize the precursor; by optimizing the concentration of wet ball milling and the parameters of spray drying, the particle size of the obtained mixture is small and uniform, which is more conducive to the formation of crystal form during calcination and improves its electrochemical performance. Through staged heating calcination and staged cooling, the crystallinity is further improved to improve the performance of lithium-rich manganese-based positive electrode materials.
[0023] 4. The preparation method of the present invention is simple and efficient. The lithium-rich manganese-based positive electrode material exhibits good stability and excellent capacity. In a wide voltage range of 2.0 to 4.8 V, it can provide a reversible capacity of 314 mAh / g at a current of 0.1C. The capacity retention rate is 93.65% after 100 cycles at a current of 1C, and the capacity retention rate is 85.14% after 300 cycles. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The scanning electron microscope images of the lithium-rich manganese-based material prepared in Example 1 of the present invention, wherein the scale of (a) is 2 μm, the scale of (b) is 1 μm, and the scale of (c) is 500 nm;
[0025] Figure 2 The scanning electron microscope images of the lithium-rich manganese-based material prepared in Comparative Example 1 of the present invention, wherein the scale of (a) is 2 μm, the scale of (b) is 1 μm, and the scale of (c) is 500 nm;
[0026] Figure 3 is an X-ray diffraction pattern of the lithium-rich manganese-based material prepared in Example 1 of the present invention;
[0027] Figure 4 This is a test chart of the lithium-rich manganese-based material prepared in Example 1 of the present invention and Comparative Example 1, which cycles 100 times at 1C current in the voltage range of 2-4.8V.
[0028] Figure 5 This is a test chart of the lithium-rich manganese-based material prepared in Example 1 of the present invention cycled 300 times at a 1C rate in the voltage range of 2-4.8V.
[0029] Figure 6 The first and second cycle charge and discharge voltage-capacity diagrams of the lithium-rich manganese-based material prepared in Example 1 of the present invention at a voltage range of 2-4.8V and a rate of 0.1C. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0031] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.
[0032] Example 1
[0033] Manganese sulfate, nickel sulfate, and cobalt sulfate were prepared into a solution with a total transition metal ion concentration of 2 mol / L according to the stoichiometric ratio of Mn:Ni:Co=0.54:0.13:0.13, added to a 1 mol / L complexing agent ammonium bicarbonate solution, heated to 55°C, and the pH was adjusted to 8 by dropping 2 mol / L sodium carbonate solution. The reaction vessel was kept sealed and stirred and heated for 24 hours. After the reaction was completed, the precipitate was collected and washed with water and dried several times.
[0034] The dried precursor and excess lithium carbonate (5 mol% excess) were dispersed in ethanol and ball-milled for 10 hours, and the solid content was controlled at 20wt%. The slurry obtained by ball milling was spray-dried under nitrogen protection (the inlet temperature of spray drying was 140°C), and potassium chloride 5 times the mass of the dried product was added for mechanical mixing, and then placed in a muffle furnace for calcination in an air atmosphere. First, it was heated to 600°C, the heating rate was 2°C / min, and the heat preservation time was 5 hours, then the temperature was raised to 850°C, the heating rate was 2°C / min, and the heat preservation time was 10 hours, and then the temperature was lowered to 300°C at a rate of 2°C / min, and the heat preservation time was 3 hours, and then it was naturally cooled. The calcined product was repeatedly washed with water, and after drying, the lithium-rich manganese-based positive electrode material Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 O 2 .
[0035] like Figure 1 As shown, it can be seen that the lithium-rich manganese-based positive electrode material particles are uniform and have good dispersion. Figure 3 This indicates that the crystal form is good. Figure 4-6 It can be seen that within the wide voltage range of 2.0 to 4.8 V, the capacity retention rate is 93.65% after 100 cycles at 1C current, and the initial discharge specific capacity is 232.2 mAh / g.
[0036] Example 2
[0037] Manganese sulfate, nickel sulfate, and cobalt sulfate were prepared into a solution with a total transition metal ion concentration of 2 mol / L according to the stoichiometric ratio of Mn:Ni:Co=0.55:0.15:0.1, added to a 1 mol / L complexing agent ammonium carbonate solution, heated to 55°C, and adjusted to pH 8 by dropping 2 mol / L sodium carbonate solution. The reaction vessel was kept sealed and stirred and heated for 24 hours. After the reaction was completed, the precipitate was collected and washed with water and dried several times.
[0038] The dried precursor and excess lithium carbonate (5 mol% excess) were dispersed in ethanol and ball-milled for 10 hours, and the solid content was controlled at 20wt%. The slurry obtained by ball milling was spray-dried under nitrogen protection (the inlet temperature of spray drying was 140°C), and potassium chloride 5 times the mass of the dried product was added for simple mechanical mixing, and then placed in a muffle furnace for calcination in an air atmosphere. First, it was heated to 600°C, the heating rate was 2°C / min, and the heat preservation time was 5 hours, then the temperature was raised to 850°C, the heating rate was 2°C / min, the heat preservation time was 10 hours, and it was cooled naturally. The calcined product was repeatedly washed with water, and after drying, the lithium-rich manganese-based positive electrode material Li 1.2 Mn 0.55 Ni 0.15 Co 0.1 O2 .
[0039] Example 3
[0040] Manganese sulfate, nickel sulfate, and cobalt sulfate were prepared into a solution with a total transition metal ion concentration of 2 mol / L according to the stoichiometric ratio of Mn:Ni:Co=0.54:0.13:0.13, added to a 1 mol / L complexing agent ammonium bicarbonate solution, heated to 55°C, and the pH was adjusted to 8 by dropping 2 mol / L sodium carbonate solution. The reaction vessel was kept sealed and stirred and heated for 24 hours. After the reaction was completed, the precipitate was collected and washed with water and dried several times.
[0041] The dried precursor and excess lithium carbonate (5 mol% excess) are dispersed in ultrapure water and ball-milled for 10 hours, and the solid content is controlled at 15wt%. The slurry obtained by ball milling is spray-dried (the inlet temperature of the spray dryer is 180°C), and 5 times the mass of potassium chloride of the dried product is added for mechanical mixing, and then placed in a muffle furnace for calcination in an air atmosphere. First, heat to 600°C, the heating rate is 2°C / min, and the heat preservation time is 5 hours, then heat to 850°C, the heating rate is 2°C / min, and the heat preservation time is 10 hours, and then cool to 300°C at a rate of 2°C / min, keep warm for 3 hours, and then cool naturally. The calcined product is repeatedly washed with water, and after drying, a lithium-rich manganese-based positive electrode material Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 O 2 .
[0042] Comparative Example 1
[0043] Manganese sulfate, nickel sulfate, and cobalt sulfate were prepared into a solution with a total transition metal ion concentration of 2 mol / L according to the stoichiometric ratio of Mn:Ni:Co=0.54:0.13:0.13, added to a 1 mol / L complexing agent ammonium bicarbonate solution, heated to 55°C, and the pH was adjusted to 8 by dropping 2 mol / L sodium carbonate solution. The reaction vessel was kept sealed and stirred and heated for 24 hours. After the reaction was completed, the precipitate was collected and washed with water and dried several times.
[0044] The dried precursor and lithium carbonate (5 mol% excess) were dispersed in ethanol and ball-milled for 10 hours, and the solid content was controlled at 20wt%. The slurry obtained by ball milling was dried in a blast drying oven, and potassium chloride 5 times the mass of the dried product was added for mechanical mixing, and then placed in a muffle furnace for calcination in an air atmosphere. First, it was heated to 600°C, the heating rate was 2°C / min, and the heat preservation time was 5 hours, then the temperature was raised to 850°C, the heating rate was 2°C / min, and the heat preservation time was 10 hours, and then the temperature was lowered to 300°C at a rate of 2°C / min, and the heat preservation time was 3 hours, and then it was naturally cooled. The calcined product was repeatedly washed with water, and after drying, the lithium-rich manganese-based positive electrode material Li1.2 Mn 0.54 Ni 0.13 Co 0.13 O 2 .
[0045] Table 1 Performance test results of Example 1 and Comparative Example 1
[0046] 1C discharge specific capacity (mAh / g) Capacity retention rate after 100 cycles (%) Example 1 232.2 93.65 Comparative Example 1 224.9 56.11
[0047] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a highly dispersed lithium-rich manganese-based positive electrode material, characterized in that: The following steps are involved: S1, introducing a transition metal salt solution, a precipitant, and a complexing agent into a reaction container to perform a coprecipitation reaction to obtain a lithium-rich manganese-based positive electrode material precursor; the transition metal salt includes a manganese salt, a nickel salt, and a cobalt salt; S2, mixing the precursor and the lithium source in a solvent by ball milling, and spray drying the mixed slurry to remove the solvent; S3, mixing the mixture obtained by spray drying with a flux evenly and then sintering in an air atmosphere, washing and drying the sintered product to obtain a lithium-rich manganese-based positive electrode material.
2. The preparation method according to claim 1, characterized in that: The chemical formula of the lithium-rich manganese-based positive electrode material is Li 1.2 Mn x Ni y Co (0.8-x-y) O2, where 0.5≤x≤0.6, 0.1≤y≤0.2, and when x=0.6, 0.1≤y<0.2, and when y=0.2, 0.5≤x<0.
6.
3. The preparation method according to claim 1, characterized in that: In step S1, the pH value of the coprecipitation reaction is 7.5 to 8.5, and the reaction is continuously stirred at 40 to 60° C. for 24 to 48 hours; In step S2, the inlet temperature of the spray drying is 135-145°C.
4. The preparation method according to claim 1, characterized in that: In step S2, the lithium source is at least one of lithium carbonate, lithium hydroxide, and lithium oxide; And / or, the solvent is at least one of water, ethanol, methanol, and isopropanol; the solid content of the mixed slurry is 10-20wt%; and the ball milling time is 5-12h, preferably 8-10h.
5. The preparation method according to claim 1, characterized in that: In step S3, the sintering includes: heating to 500°C-600°C at 2-10°C / min, and keeping warm for 4-6 hours; then heating to 800°C-900°C at 2-10°C / min, and keeping warm for 10-14 hours; preferably, finally cooling to 250°C-350°C at 2-10°C / min, keeping warm for 2-4 hours, and then cooling naturally.
6. The preparation method according to claim 1, characterized in that: In step S1, the nickel salt is at least one of nickel sulfate and nickel acetate; the manganese salt is at least one of manganese sulfate and manganese acetate; and the cobalt salt is at least one of cobalt sulfate and cobalt acetate.
7. The preparation method according to claim 1, characterized in that: In step S1, the precipitating agent is at least one of sodium carbonate, potassium carbonate, sodium hydroxide and potassium hydroxide; the complexing agent is at least one of ammonium carbonate, ammonium sulfate and ammonium bicarbonate.
8. The preparation method according to claim 1, characterized in that: In step S3, the flux is at least one of sodium chloride, potassium chloride, lithium chloride and lithium nitrate.
9. A highly dispersed lithium-rich manganese-based positive electrode material, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the highly dispersed lithium-rich manganese-based positive electrode material according to claim 9 as a positive electrode for a lithium-ion battery.
Citation Information
Patent Citations
Preparation method of layered lithium-rich manganese base oxide of positive material of lithium ion battery
CN102683645A
Method for preparing high-capacity lithium-rich manganese-based positive electrode material through ammoniation-free coprecipitation
CN111987305A
Cited By
Lithium-rich manganese-based positive electrode material and preparation method thereof, battery positive electrode and lithium battery
CN121778793A